S103 Neutrophil trans-epithelial migration in cystic fibrosis airways. (14th November 2013) - Rebeyrol, C; Porter, JC
Abstract : Background: Lung injury in cystic fibrosis (CF) is caused by recurrent airway infection and inflammation partially due to the massive infiltration of neutrophils in airways. The processes regulating neutrophil migration across the bronchial and the alveolar epithelia are poorly understood especially in CF. The aim of this study is to analyse the adhesion molecules expressed by neutrophils and epithelial cells during the neutrophil trans-epithelial migration through the bronchial epithelium. We have already shown that ICAM-2, previously thought to be present only on endothelial cells, is also expressed on the bronchial epithelium and plays a key role in T cell migration 1 . Objectives: We investigated whether ICAM-2 regulates neutrophil trans-epithelial migration through the bronchial barrier. Methods: We have used human bronchial epithelial cell lines and primary human bronchial epithelial cells (HBECs) from non CF and CF patients, at baseline and on TNF-α exposure for 24h. Results: We have shown a constitutive expression of ICAM-2 at the basal side of the primary HBECs grown at air-liquid interface for 21 days. A significant 4-fold increase in ICAM-2 mRNA expression was observed 24h after TNF-α treatment in non CF cell line and primary HBECs. Moreover, from confocal microscopy and immunoblots, we have found that ICAM-2 protein expression is statistically up-regulated 24h after TNF-α treatment. We have performed the same experiments in non CF and CF paraffin embedded lung sections and we demonstrated a significant increase in ICAM-2 expression in CF. It has previously been pointed out that in CF cells there is actin disorganisation and disruption of the tight junctions leading to an increase in the neutrophil migration 2 . Our preliminary data showed that interaction neutrophil-epithelium provokes an actin remodelling that we can avoid using an ICAM-2 blocking antibody prior the contact with neutrophils. Conclusions: ICAM-2 mRNA and protein levels are higher in CF lung sections and in non CF cells treated with TNF-α than in controls. Understanding the interactions neutrophil-epithelium in CF could prevent neutrophil accumulation in airways and attenuate lung injury. References: Porter & Hall, FASEB J ., 2009 Castellani et al., Lab Invest ., 2012